Neuropsychic Mechanism in the Etiopathogenesis of Bronchial Asthma and Existing Methods of Psychotherapy of Bronchial Asthma (Eurasian Medical Research Periodical, 2022)
In this article, information about neuropsychic mechanism in .the etiopathogenesis of bronchial asthma and methods of psychotherapy is given. Neuropsychic disorders plays an important role in the development of bronchial asthma as well as the relationship with family and other emotional problems whichcan be treated by using various methods of physicians.